The Characteristic of Groundwater Table and Subsidence of Degraded Peatland in Ex ICCTF Plot Central Kalimantan - Muhammad Anang Firmansyah; Wahyu Adi Nugroho (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2020)
Degraded peatlands typically have been cultivated by communities for agriculture. Ex ICCTF plot in Jabiren is considered as a degraded peatland since the area has been cultivated and drained for smallholder plantation. This study aimed to characterise the groundwater level and peat subsidence periodically over seven months of observation. It has been found that the groundwater level fluctuated from 50 cm to 150 cm below the peat surface, implying the deterioration of peat ecosystem. Based on the transect observation, the groundwater table seems to form a dome shape with the deeper level existed adjacent to the canal. The average peat subsidence was around 27 to 39 cm in cumulative since the subsidence stick installation. However, in the range of ten-month of observation, the peat subsidence was around 8.5 cm. The subsidence was higher on the location adjacent to the canal (25 m) compared to the farther one (100 m). The subsidence also fluctuated, notably in the wet season, indicating the influence of rain event to peat subsidence.  Rewetting peatland was likely to result in reducing peat subsidence suggesting the importance of water management in peatland to recover degraded peatland.